Establishment of an avian leukosis virus subgroup A-resistant cell line - Min FENG; Man-man DAI; Ming LIAO; Wei-sheng CAO (Journal of Integrative Agriculture)
Rapid diagnostic methods for classifying avian leukosis subgroups in the field were needed for routine, large-scale screening. As a first step in method development, we inserted the avian leukosis virus subgroup A (ALV-A) env gene into plasmid pcDNA3.1/Zeo (+) and used this construct to transfect DF-1 cells. Zeocin-resistant cells were obtained after 2 weeks of zeocin selection. Then, the cells were analyzed using PCR, immunofluorescence, and Western blot for expression of the envA-encoded envelope protein after 30 serial passages. The DF-1/A cell line was completely resistant to 104 TCID50/0.1 mL (50% tissue culture infective dose) ALV-A and was partially resistant to 105 TCID50/0.1 mL ALV-A viral particles. By comparing the DF-1/A and DF-1 cell lines, an ALV-A isolate was identified using a gag-specific ELISA for capsid protein p27. Thus, we established a DF-1/A cell line that was resistant to ALV-A infection. This cell line will be useful as a diagnostic tool.